Effect of Sodium Alginate Coating with Ascorbic Acid on Shelf Life of Raw Pork Meat - Gammariello, D; Incoronato, A. L; Conte, A; Nobile, M. A Del (Journal of Food Technology Research, 2015)
The focus of this study was to evaluate the effect of sodium alginate coating loaded with ascorbic acid on shelf life of raw pork meat slices, used to prepare skewers. To the aim, the meat samples were first dipped in the sodium lactate solution (40% w/w) and then divided into 3 treatment groups: (i) control samples (dipped meat), (ii) coated meat, (iii) coated meat containing ascorbic acid (i.e. 500, 1000 and 1500 ppm). All samples were packaged under modified atmosphere packaging (50%O2/30%CO2/20%N2) and stored at 4±2°C. The samples were analysed for sensory and microbiological characteristics. The combination of dipping, active coating and MAP improved the sensory quality of packaged skewers. In contrast active coating does not considerable effect in slowing down the growth of spoilage microorganisms. Sample coated with 1500 ppm ascorbic acid displayed the longest shelf life, equal to 8.9 days, which was about 60% longer than the control.